Special Editions of Full Prof. Dusko Bjelica, PhD: 1992-2020 - Milena Mitrovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
Dusko Bjelica, PhD, a full professor at the University of Montenegro, has a large number of professional and scientific publications. The main aim of this paper was to search and list his special editions (books). We found the editions by searching his biography and reports on scientific research. There were a total of 65 issues, which we divided into monographs, textbooks and scientific studies. Of the total, 38 are monographs, 25 textbooks and two scientific studies, representing the fields of sports, especially football and sport training. In his books, Professor Bjelica was most concerned with the development of football in Montenegro, sports training, physical culture, but also notable Montenegrin athletes and complex sporting phenomena, such as the bouncing of sport balls and the accuracy of hitting the ball. These numbers, as well as the various topics within these fields, show the quality of the scholarly work of the author. The classification is also significant given the abundance of Professor Bjelica works; therefore, it will enable easier literature searches and better insight into the subject matter of the books.